2015
DOI: 10.1002/cbdv.201400273
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Chemical Diversity of Southeast European Populations of Salvia officinalis L.

Abstract: The essential oils of 25 populations of Dalmatian sage (Salvia officinalis L.) from nine Balkan countries, including 17 indigenous populations (representing almost the entire native distribution area) and eight non-indigenous (cultivated or naturalized) populations were analyzed. Their essential-oil yield ranged from 0.25 to 3.48%. Within the total of 80 detected compounds, ten (β-pinene, 1,8-cineole, cis-thujone, trans-thujone, camphor, borneol, trans-caryophyllene, α-humulene, viridiflorol, and manool) repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…The absence of this compound may be regarded as a positive aspect because it is associated with the off‐flavours produced by contamination with mold. Cvetkovikj et al . found a high degree of variability among SoEOs from south‐eastern Europe, even with regard to the main components.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of this compound may be regarded as a positive aspect because it is associated with the off‐flavours produced by contamination with mold. Cvetkovikj et al . found a high degree of variability among SoEOs from south‐eastern Europe, even with regard to the main components.…”
Section: Resultsmentioning
confidence: 99%
“…According to Alonso (1998), the sage's EO content commonly ranges from 0.4 to 1.0%. However, Cvetkovikj et al (2015) found EO content variation of 0.25 to 3.48% among twenty-five samples of sage plants across nine Southeast European countries. Govahi et al (2015) observed an averaged EO content of 1.86% in sage plants cultivated under different doses of fertilizers and subjected to water stress.…”
Section: Content and Composition Of The Essential Oilmentioning
confidence: 87%
“…El 46 % de su contenido está constituido de 1,8-cineol, α-tujona y β-cariofileno. En una muestra extraída de una planta del Valle del Cauca se encontraron β-cariofileno y α-copaeno como los constituyentes mayoritarios (Saldarriaga et al, 2009) y los mismos terpenos se identificaron en AEs de plantas de otros países (Cvetkovikj et al, 2015). La actividad antiproliferativa del AE puede deberse a la presencia de estos terpenos, el 1-8-cineol mostró eficacia para inhibir el desarrollo de cáncer colorectal en ratones (Murata et al, 2013) y de los otros terpenos existe evidencia de la actividad anticancerígena como se mencionó.…”
Section: Discussionunclassified